Melatonin ameliorates degenerative alterations caused by age in the rat prostate and mitigates high-fat diet damages - Tamarindo, Guilherme H. [UNESP]; Gobbo, Marina G. [UNESP]; Taboga, Sebastiao R. [UNESP]; Almeida, Eduardo A. [UNESP]; Goes, Rejane M. [UNESP] (Wiley-Blackwell, 2020)
Imbalance of sexual steroids milieu and oxidative stress are often observed during aging and correlated to prostate disorders. Likewise, high-fat intake has been related to prostate damage and tumor development. Melatonin (MLT) is an antioxidant whose secretion decreases in elderly and is also suggested to protect the gland. This study evaluated the impact of a long-term high-fat diet during aging on prostate morphology and antioxidant system of rats and tested the effects of MLT supplementation under these conditions. Male rats were assigned into four groups: control, treated with MLT, high-fat diet and high-fat diet treated with MLT. The high-fat diet was provided from the 24th week of age, MLT from the 48th (100 mu g/kg/day) and rats were euthanized at the 62nd week. The high-fat diet increased body weight, retroperitoneal fatness, glycaemia, and circulating estrogen levels. It aggravated the aging effects, leading to epithelial atrophy (similar to 32% reduction of epithelial height) and collagen fibers increase (83%). MLT alone did not alter biometric and physiological parameters, except for the prostate weight decrease, whereas it alleviated biometric as well as ameliorated acinar atrophy induced by high-lipid intake. Systemic oxidative stress increased, and prostatic glutathione peroxidase activity decreased fivefold with the high-fat diet despite the indole. Regardless of the diet, MLT triggered epithelial desquamation, reduced androgen receptor-positive cells, increased smooth muscle layer thickness (12%), decreased at least 50% corpora amylacea formation, and stimulated prostatic gluthatione-S-transferase activity. In conclusion, MLT partially recovered prostate damage induced by aging and the long-term high-fat diet and ameliorated degenerative prostate alterations.
Keywords: aging; GST; high-fat; melatonin; oxidative stress; prostate